Understanding Ecological Agricultural Technology Adoption in China Using an Integrated Technology Acceptance Model—Theory of Planned Behavior Model - Dong, Hao; Wang, Huanyuan; Han, Jichang (Frontiers in Environmental Science, 2022)
With the development of the economy and society, environmental pollution and resource waste problems are emerging, especially in agricultural production, and the adoption of ecological agricultural technologies is a prerequisite to alleviate ecological pressure. Based on the Technology Acceptance Model - Theory of Planned Behavior (TAM-TPB) and using research data from Hubei, Hunan, and Anhui provinces, this paper empirically analyzes the factors influencing farmers' intention to adopt rice and shrimp crop technologies using the PLS-SEM method. The configuration path of high technology intention was further investigated by the fsQCA method. The results showed that: (i) farmers' intention to adopt rice-shrimp crop technology was mainly positively influenced by behavioral attitude, subjective norm, perceived behavioral control, behavioral attitude; (ii) Perceived usefulness and perceived ease of use had a direct effect on farmers' intention to adopt and an indirect effect with behavioral attitude as a mediating variable, while perceived ease of use had a positive effect and perceived usefulness did not. In doing so, four configuration paths of high technology acceptance intention were obtained. Given this, this paper makes relevant suggestions, suggesting that the relevant departments focus on the comprehensive benefits of rice-shrimp crop technology; agricultural technology departments provide technical assistance to farmers, and village committees organize regular inter-farmer exchanges.